Zinzendorf und die Reformation - Kröger, Rüdiger (Unitas Fratrum, 2018)
In the absence of systematic statements by Zinzendorf about this theme, the article approaches it from two sides. Zinzendorf experienced the bicentennial celebrations of the Reformation events. In diaries, poetry and cantatas he is critical of the events and celebrations and of the situation in church and so ciety. In 1717 distance from the official ceremonies in Wittenberg and alienation from the behaviour of those around him predominated: instead of celebrating, the student Zinzendorf composed a lament. In 1730 Zinzendorf was the lord of the manor of Berthelsdorf und Herrnhut. In an original responsory between the congregation, Paul and personalities of the Reformation era he helped his subjects to understand the objectives of the Reformation. In a cantata based on the sermon text the congregation participates actively in the experiences whereby Zinzendorf found the justification of the sinner through the wounds of Jesus. In subsequent years, after his entry into the clergy and against a background of continuing hostility, engagement with the Augsburg Confession - on which he published a commentary in 1735, which he versified in 1745, and on which he based a series of lectures in 1747 - was repeatedly of importance for Zinzendorf. Scattered references in Zinzendorf s addresses give an indication of his understanding of the Reformation and his relationship to Luther. Zinzendorf distinguishes between two offices that cannot be combined - namely, that of the Reformer who must gather many people, above all those with great influence, behind him, and that of the gatherer of the congregation, whose task is to establish the fellowship between the children of God from different confessions and nations without which the Reformation would not be com plete. It is also precisely in his engagement with the biblical text and his use of song and catechism that Zinzendorf sees himself as a true pupil of Luther